Culture Culture as a Structural System: A Semiotic Analysis of American Symbols in Tokyo Disneyland Japan - Saiyidinal Firdaus (Southeast Asian Language and Literature Studies, 2025)
This study examines how American cultural symbols operate in Tokyo Disneyland Japan by conceptualizing culture as a structural semiotic system rather than a collection of localized representations. Departing from approaches that emphasize cultural hybridity or adaptation, the study asks how American myths are selected, organized, and naturalized within a Japanese context through systemic semiotic mechanisms. Employing a qualitative interpretive design, the research integrates structural cultural semiotics, myth analysis, and multimodal spatial analysis to examine themed zones, architectural forms, visual symbols, textual narratives, and routinized visitor practices across the park. The findings demonstrate that Tokyo Disneyland mobilizes a selective repertoire of American cultural myths—civic nostalgia, frontier morality, technological optimism, and moralized fantasy—which are abstracted from historical and political specificity. These symbols derive meaning not in isolation, but through their relational positioning within a coherent semiotic structure characterized by spatial hierarchy, binary opposition, and narrative sequencing. Furthermore, the study shows that American symbols are naturalized in Japan not primarily through localization, but through decontextualization, affective orchestration, ritualization, and multimodal coherence, which collectively neutralize ideological visibility and minimize cultural friction. The study contributes theoretically by advancing a structural understanding of culture as a regulated system of signs and methodologically by offering a replicable framework for analyzing global cultural spaces as semiotic formations. It underscores the importance of structure in mediating cultural meaning and power in transnational entertainment environments.